Low-Scale Expression and Purification of an Active Putative Iduronate 2-Sulfate Sulfatase-Like Enzyme from Escherichia coli K12 - Morales Álvarez, Edwin David (2013)
The sulfatase family involves a group of enzymes with a large degree of similarity. Until now, sixteen human sulfatases have been identified, most of them found in lysosomes. Human deficiency of sulfatases generates various genetic disorders characterized by abnormal accumulation of sulfated intermediate compounds. Mucopolysaccharidosis type II is characterized by the deficiency of iduronate 2-sulfate sulfatase (IDS), causing the lysosomal accumulation of heparan and dermatan sulfates. Currently, there are several cases of genetic diseases treated with enzyme replacement therapy, which have generated a great interest in the development of systems for recombinant protein expression. In this work we expressed the human recombinant IDS-Like enzyme (hrIDS-Like) in Escherichia coli DH5α. The enzyme concentration revealed by ELISA varied from 78. 13 to 94. 35 ng/ml and the specific activity varied from 34. 20 to 25. 97 nmol/h/mg. Western blotting done after affinity chromatography purification showed a single band of approximately 40 kDa, which was recognized by an IgY polyclonal antibody that was developed against the specific peptide of the native protein. Our 100 ml-shake-flask assays allowed us to improve the enzyme activity seven fold, compared to the E. coli JM109/pUC13-hrIDS-Like system. Additionally, the results obtained in the present study were equal to those obtained with the Pichia pastoris GS1115/pPIC-9-hrIDS-Like system (3 L bioreactor scale). The system used in this work (E. coli DH5α/pGEX-3X-hrIDS-Like) emerges as a strategy for improving protein expression and purification, aimed at recombinant protein chemical characterization, future laboratory assays for enzyme replacement therapy, and as new evidence of active putative sulfatase production in E. coli. © 2013 The Microbiological Society of Korea and Springer-Verlag Berlin Heidelberg.